2023 Inaugural Healthcare Delivery Science: Innovation and Partnerships for Health Equity Research (DESCIPHER) Symposium - Allison Z. Orechwa; Anshu Abhat; Lilyana Amezcua; Bernadette Boden‐Albala; Thomas A. Buchanan; Steve Chen; Lauren P. Daskivich; Brett Feldman; Michael K. Gould; Wei‐an Lee; Christopher Lynch; Carolyn C. Meltzer; et al. (Wiley, 2024)
Abstract Introduction This article provides an overview of presentations and discussions from the inaugural Healthcare Delivery Science: Innovation and Partnerships for Health Equity Research (DESCIPHER) Symposium. Methods The symposium brought together esteemed experts from various disciplines to explore models for translating evidence‐based interventions into practice. Results The symposium highlighted the importance of disruptive innovation in healthcare, the need for multi‐stakeholder engagement, and the significance of family and community involvement in healthcare interventions. Conclusions The article concluded with a call to action for advancing healthcare delivery science to achieve health equity.